Mechanism analysis of the immobilization of heavy metal ions with the water-soluble polymer: The influence of resin structure and the further adsorption of chelate. (15th January 2022) - Miao, Chen; Jiang, Jia-Yu; Liu, She-Jiang; Wang, Yu-Jing; Zhang, Kai
Abstract: Polymer materials have become one of the potential materials for remediation of heavy metal (HM) contamination in water and soil. However, the specific advantages of polymers are rarely studied. Water-soluble thiourea formaldehyde resin (WTF) is one of the effective polymer amendments. Through leaching experiments, WTF can stabilize 93.0% of Cd 2+ and 99.7% of Cu 2+ . The results of HM morphology analysis show that after adding WTF, most of the HMs have been transformed into a relatively stable state. For example, in the process of remediation of 6 mg/kg Cd contaminated soil, the proportion of acid-soluble Cd decreased from 56.5% to 12.8%, and the residual state increased from 13.5% to 45.4%. Compared with the resin-free structure, the three-dimensional structure of the resin plays an important role, but the efficiency of precipitation with HMs is doubled. According to the simulation of the adsorption process by Materials Studio, the characterization of the scanning electron microscope-energy dispersive instrument and the results of the adsorption experiment, in the solution, the precipitate formed by WTF and Cd 2+ has multilayer adsorption of HMs, and can further adsorb HM by –OH. Soil enzyme activity experiments proved that the risk of secondary pollution by adding WTF is rare, and even WTF can achieve the effect of slow-release nitrogen fertilizer. In the WTF remediation process, the biological toxicity reduction of HMs is result from, on the one hand, the complexation of functional group of WTF; on the other hand, the resin structure of WTF; in addition, multi-layer adsorption and adsorption of end groups in the precipitation formed by WTF and HM. This work provides a theoretical basis for the potential capabilities of water-soluble resins and is beneficial to the design and development of subsequent amendments. Graphical abstract: Image 1 Highlights: The stability rates of Cd and Cu reached 93.0% and 99.7%, respectively. Compared with NRTH, the resin structure of WTF increases the stabilization ability. HMs can be further removed by WTF chelate in the way of multilayer adsorption. The monomer of WTF can bind to the active sites 330 and 334 of urease. The soil nutrient cycle changes positively with the addition of WTF.